AB0102 The ginger derivative 6-shogaol as a treatment in osteoarthritis.modulation of chondrocyte hypertrophy and matrix calcification. (12th June 2018) - Gratal, P.; Lamuedra, A.; Mediero, A.; Herrero-Beaumont, G.; Largo, R.
Abstract : Background: Osteoarthritis (OA) is a complex joint disease characterised by a progressive lost of articular cartilage (AC), synovial inflammation and subchondral bone alterations. The latest theories of OA pathogenesis implicate the interplay between mechanical damage and chronic inflammation that has been associated to the activation of the innate immune system, intricately involved in the development of this low-grade inflammation. During the course of OA, Toll like receptor (TLR) activation has been related to the release of cytokines and inflammatory mediators, which further aggravate synovitis and AC damage. 1 In this scenario, hyaline chondrocytes seem to acquire a hypertrophic-like phenotype associated to AC degradation. 6-shogaol (6S), an effective anti-inflammatory Ginger derivative, is able to inhibit TLR4-mediated innate immune responses. 2 Objectives: Our aim was to study the therapeutic benefit of 6-shogaol studying its anti-inflammatory effects in an OA mice model, and in the modulation of hypertrophic markers in chondrocyte cultures. Methods: C57BL/6 male mice were randomly assigned to two groups: control (n=7) and OA (n=17). OA was induced by transection of the medial menisco-tibial ligament. Nine OA mice started receiving 6S (15 mg/kg/day; OA +6S) since surgery. After 8 weeks, animals were euthanized and joints were collected. Chondrogenic differentiation was induced in vitro in the pre-chondrogenic cell line ATDC5 in presence or absence of 5 × 10–6M 6S. Gene expression of hypertrophic markers, as well as mineralization and proteoglycan synthesis were determined. Results: Both synovial inflammation and AC damage were more severe in OA animals (Control: 0.1±0.1; OA: 3.0±0; p<0.005, and Control: 0.5±0.2, OA: 5.4±0.6; p<0.005, respectively) with a significant reduction in OA+6S animals (2.4±0.2; p<0.05 and 2.6±0.5 p<0.01 vs. OA, respectively). Collagen X and MMP13 immunohistochemistry showed an increase in the AC of OA and OA-6S mice, while a significant reduction was found in 6S-treated mice (ColX: Control: 0.13±0.03, OA: 0.93±0.1; OA-6S: 0.43±0.1; p<0.05 and MMP13: Control: 0.35±0.1, OA: 0.68±0.1, OA-6S: 0.28±0.07, p<0.05). Similar results were found in the synovium and meniscus for these two markers. 6S was able to significantly inhibit the expression of Collagen X, Ihh and MMP13 in ITS-stimulated cells after 14 and 21 days of culture. Furthermore, 6S prevented the increase in mineralization and proteoglycan synthesis in ITS-stimulated ATDC5 cells after 14 days of culture (p<0.05), as seen by Alizarin red and Alcian blue staining, respectively. Conclusions: Our results showed that 6S significantly prevented cartilage degradation and synovial inflammation, in parallel to a reduction in the presence of hypertrophic markers in the cartilage of OA mice. In vitro, 6S inhibited the chondrogenic differentiation of ATDC5 cells. These results suggest that 6S could work as a good treatment in OA both inhibiting differentiation markers and reducing the severity of joint damage in an OA murine model. References: [1] Gómez R, et al. Nat Rev Rheumatol2015. [2] Villalvilla A, et al. J Mol Nutr Food Res2013. Disclosure of Interest: P. Gratal: None declared, A. Lamuedra: None declared, A. Mediero Grant/research support from: CP15/00053 PI16/00991, G. Herrero-Beaumont Grant/research support from: PI16/00065, R. Largo Grant/research support from: PI15/00340